ANALYSIS OF THE USE OF E-COMMERCE AND ITS IMPACT ON CONSUMER SATISFACTION AT MAWAR BAKERY AND CAKE SHOP, KATAMSO MEDAN BRANCH - puspitasari, angelin; Sri Rezeki; Muammar Rinaldi (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
Mawar Bakery and Cake Shop Medan is a company that operates in the field of food sales with the main focus being bread and cakes. The products sold from this shop consist of sponge cake, plain bread & jam, various donuts, small breads, special cakes, various pies and pastries. The aim of this research is to determine the influence of e-commerce, digital payments and e-service quality on consumer satisfaction at the Mawar Bakery and Cake Shop Medan store. This type of research uses quantitative research, the data source in this research is a primary data source, the population in this research is all consumers who make purchases at Mawar Bakery and Cake Shop Medan, the number of which cannot be known and the sample in the research is 97 samples obtained using Lemeshow formula which is used to calculate samples in conditions where the population is unknown. Data collection techniques through questionnaires using Likert scale measurements.